Expression of epidermal growth factors and apoptosis markers in pancreatic ductal adenocarcinoma. - Jolanta Czyzewska; Katarzyna Guzińska-Ustymowicz; Anna Pryczynicz; Andrzej Kemona (Folia Histochemica et Cytobiologica, 2010)
BACKGROUND Epidermal growth factor family members: EGF, EGFR and the c-erbB-2(HER-2/neu) are involved in the growth of pancreatic ductal carcinoma, its invasiveness and metastases. Similarly, proteins regulating apoptosis can influence the development of pancreatic cancer. The aim of our study was to assess the expressions of EGF, EGFR, c-erbB-2, Bax and Bcl-xL in comparison with anatomo-clinical parameters. We also analyzed the relationship between the epidermal growth factors and apoptosis-regulating proteins. MATERIALS AND METHODS The levels of these proteins were determined immunohistochemically in 29 pancreatic ductal carcinoma cases. RESULTS We found no correlation of EGF, EGFR, c-erbB-2, Bax and Bcl-xL with age and gender of patients, or histological type and grade of malignancy (G). However, we observed a very strong correlation between EGF, EGFR, Bax, Bcl-xL and lymph node metastases (p=0.000, p=0.001, p=0.008, p=0.012, respectively) and between EGF, EGFR and distant metastases (p=0.002, p=0.008, respectively). Moreover, we found a correlation between Bcl-xL and c-erbB-2 (p=0.030) and between EGF and Bax (p=0.041). CONCLUSIONS These investigations seem to suggest that both epidermal growth factors (EGF, EGFR) and apoptosis-regulating proteins (Bax and Bcl-xL) play an essential role in lymph node involvement. Moreover EGF and EGFR are involved in distant metastases. The apoptosis markers appear to cooperate with epidermal growth factor proteins in the process of tumor spread.